CACNA1H antibodies associated with headache with neurological deficits and cerebrospinal fluid lymphocytosis (HaNDL). (January 2013) - Kürtüncü, Murat; Kaya, Dilaver; Zuliani, Luigi; Erdağ, Ece; İçöz, Sema and Uğurel, Elif and Çavuş, Filiz and Ayşit, Neşe and Birişik, Ömer and Vincent, Angela and Eraksoy, Mefkure and Vural, Burçak and Akman-Demir, Gülşen and Tüzün, Erdem
Background: Patients with the syndrome of headache with neurological deficits and lymphocytosis (HaNDL) typically present with recurrent and temporary attacks of neurological symptoms and cerebrospinal fluid lymphocytosis. Aim and methods: To identify potential HaNDL‐associated antibodies directed against neuronal surface and/or synapse antigens, sera of four HaNDL patients and controls were screened with indirect immunohistochemistry, immunofluorescence, cell-based assay, radioimmunoassay, protein macroarray and enzyme-linked immunosorbent assay (ELISA). Results: Although HaNDL sera did not yield antibodies to any of the well-characterized neuronal surface or synapse antigens, protein macroarray and ELISA studies showed high-titer antibodies to a subunit of the T-type voltage-gated calcium channel (VGCC), CACNA1H, in sera of two HaNDL patients. Conclusion: Our results support the notion that ion channel autoimmunity might at least partially contribute to HaNDL pathogenesis and occurrence of neurological symptoms.